Biosurfactants, natural alternatives to synthetic surfactants: Physicochemical properties and applications - Jahan, Ruksana; Bodratti, Andrew M.; Tsianou, Marina; Alexandridis, Paschalis (Advances in colloid and interface science, 2020)
Biosurfactants comprise a wide array of amphiphilic molecules synthesized by plants, animals, and microbes. The synthesis route dictates their molecular characteristics, leading to broad structural diversity and ensuing functional properties. We focus here on low molecular weight (LMW) and high molecular weight (HMW) biosurfactants of microbial origin. These are environmentally safe and biodegradable, making them attractive candidates for applications spanning cosmetics to oil recovery. Biosurfactants spontaneously adsorb at various interfaces and self-assemble in aqueous solution, resulting in useful physicochemical properties such as decreased surface and interfacial tension, low critical micellization concentrations (CMCs), and ability to solubilize hydrophobic compounds. This review highlights the relationships between biosurfactant molecular composition, structure, and their interfacial behavior. It also describes how environmental factors such as temperature, pH, and ionic strength can impact physicochemical properties and self-assembly behavior of biosurfactant-containing solutions and dispersions. Comparison between biosurfactants and their synthetic counterparts are drawn to illustrate differences in their structure-property relationships and potential benefits. Knowledge of biosurfactant properties organized along these lines is useful for those seeking to formulate so-called green or natural products with novel and useful properties. [Display omitted] •Biosurfactants are amphiphiles of microbial origin with surface active properties.•Biosurfactant solution self-assembly is modulated by pH, T, and ionic strength.•Diverse chemical structure/composition is reflected in solution association.•Surfactant properties of biosurfactants can be superior to synthetic surfactants.•Biosurfactants show promise in bioremediation, oil recovery, and pharmaceuticals.